Resistance and the city : negotiating urban identities: race, class, and gender - Ehland, Christoph; Fischer, Pascal (Spatial practices : an interdisciplinary series in cultural history, geography and literature, 2018)
"The contributions collected in the second volume of Resistance and the City are devoted to the three markers of identity that cultural studies has recognised as paramount for our understanding of difference, inequality, and solidarity in modern societies: race, class, and gender. These categories, tightly linked to the mechanics of power, domination and subordination, have often played an eminent role in contemporary struggles and clashes in urban space. The confluence of people from diverse ethnic, social, and sexual backgrounds in the city has not only raised their awareness of a variety of life concepts and motivated them to negotiate their own positions, but has also encouraged them to develop strategies of resistance against patterns of social and spatial exclusion. Contributors: Oliver von Knebel Doeberitz, Barbara Korte, Anna Lienen, Gill Plain, Frank Erik Pointner, Katrin Röder, Ingrid von Rosenberg, Mark Schmitt, Ralf Schneider, Christoph Singer, Sabine Smith, Merle Tönnies, Ger Zielinski"--